A legal perspective on the non-consensual dissemination of sexual images: Identifying strengths and weaknesses of legislation in the US, UK and Belgium. (December 2016) - Beyens, Jolien; Lievens, Eva
Abstract: Non-consensual dissemination of sexual images, often denoted as 'revenge porn', can be described as the act of distributing photos or videos depicting individuals in sexually suggestive or explicit circumstances without consent. The harmful impact can be felt both in the private and professional spheres of victims. Questions were raised across jurisdictions regarding the applicability of existing criminal law provisions or the need for legislative initiatives. After analysing the terminology and scope, this article examines three US state level dedicated laws, the amended UK Criminal Justice and Courts Act, and a dedicated provision in the Belgian Criminal Code. This analysis results in the identification of key elements that could serve as guidance for legislators to amend or adopt criminal legislation. Such provisions should include clearly delineated definitions, acknowledge that the lack of consent of the pictured person is the trigger for criminalisation, provide for relevant defences, and integrate sufficiently deterrent sanctions.